Verifikasi Logam Berat K (Kalium) dengan Metode Flame Spektrofotometri Serapan Atom (SSA) - Pratiwi, Mutiara; Syawal, M Ichlas (Darul Yasin Al Sys, 2023)
The method verification aims to guarantee quality, method suitability and compliance with laboratory regulations. This research wa conducted to confirm and evaluate whether the test method used was suitable for its use or not. The parameters of this verification, accuracy, limit of detectin (LoD), limit of quantification (LoQ) and control chart. The standart deviaton value of the side of the tool for metal K is 0.008, so it can be sait that the Flame Atomic Absorption Spechtrophotometer tool is very good for testing metal K. The result of the linearity test show that the R2 value for K metal is 0.9993, meaning that standart is quite accurate because in industry the permitted range of regression values is 0.995-1.000. The LoD value of K metal is 0.0672 and LoQ is 0.2236. Judging from the % RCE data obtained, it shows that the concentration of the K metal series is suitable for use because it is in accordance with the tool’s capabilities, which is less than 1%. The calculation results explain that all the verification test parameters of the method used are suitable for their use.